Prion protein amino acid sequence influences formation of authentic synthetic PrPSc - Alyssa J. Block; Taylor C. York; Romilly Benedict; Jiyan Ma; Jason C. Bartz (Scientific Reports, 2023)
Abstract Synthetic prions, generated de novo from minimal, non-infectious components, cause bona fide prion disease in animals. Transmission of synthetic prions to hosts expressing syngeneic PrPC results in extended, variable incubation periods and incomplete attack rates. In contrast, murine synthetic prions (MSP) generated via PMCA with minimal cofactors readily infected mice and hamsters and rapidly adapted to both species. To investigate if hamster synthetic prions (HSP) generated under the same conditions as the MSP are also highly infectious, we inoculated hamsters with HSP generated with either hamster wild type or mutant (ΔG54, ΔG54/M139I, M139I/I205M) recombinant PrP. None of the inoculated hamsters developed clinical signs of prion disease, however, brain homogenate from HSPWT- and HSPΔG54-infected hamsters contained PrPSc, indicating subclinical infection. Serial passage in hamsters resulted in clinical disease at second passage accompanied by changes in incubation period and PrPSc conformational stability between second and third passage. These data suggest the HSP, in contrast to the MSP, are not comprised of PrPSc, and instead generate authentic PrPSc via deformed templating. Differences in infectivity between the MSP and HSP suggest that, under similar generation conditions, the amino acid sequence of PrP influences generation of authentic PrPSc.